THE INFLUENCE OF MARKET NETWORK DYNAMICS ON DEVELOPMENT OF MARKET ARCHITECTURE IN PALEMBANG - Dwinda, Syahfira
The locations of the governmental centers of the Palembang Sultanate were situated along the riverbanks. The river played a crucial role in the life of the sultanate, serving as a source of sustenance, providing accessibility, and functioning as a transportation and communication route. The limited space along the riverbanks led to the expansion of the sultanate's centers along the river since the inland areas were still forested and less secure. The rapid development of global trade activities during the sultanate's reign made the river routes increasingly busy with local, regional, and international traders. The presence of the Dutch trading company (VOC) and later the Dutch East Indies government also influenced the development of governmental and commercial activities in the Palembang Sultanate. The colonial policies introduced physical market buildings, whereas previously trade occurred on the water or in simple open spaces (cungkukan). The development of markets in Palembang continued to progress, often situated along the banks of the Musi River. The aim of this research is to understand the dynamics of market networks in relation to the development of market architecture. The research was conducted using historical tracing methods to understand the development of the trade network system, i.e., markets, and its correlation with the historical formation and development of market architecture in Palembang. The research findings indicate that the system and role of market networks as trade networks influenced the development of architecture and even the structural layout of Palembang city, with its ulu-ilir system and the spatial structure of the central area of Palembang city being limited and expanding along the riverbanks.